Potential advantages and disadvantages of using creatine supplements by professional volleyball players - Sieroń, Adrian; Kołodyńska, Gabriela; Rostojek, Paulina (Journal of Education, Health and Sport, 2018)
Creatine, a peptide built from three amino acids: arginine, glycine and methionine, is one of the most popular diet supplements used by people who train not only strength sports but also other popular disciplines, including team sports, i.a. volleyball. The benefits of creatine supplementation, such as weight, strength and muscle mass gain, are widely known, which translates directly into improved sports performance. However, is it really possible to consider such supplementation as a model solution for absolutely every athlete practicing volleyball? This brief review was intended to summarize the indications and effects of supplementation of volleyball players with creatine, taking into account the theoretical side of potential benefits, i.e. creatine metabolism in the creatine kinase (CK)-phosphocreatine (PCr) system and energetic advantages for muscle cells coming from the "renewing" of the basic useful energy carrier that is ATP (transferring the phosphate group to ADP) by creatine phosphate, as well as visual effects of training achieved in practice by volleyball players after supplementation with creatine, taken mostly in the form of monohydrate. This work also reviews possible potential side effects that are usually the result of exceeding the recommended dose of a supplement or taking preparations that are not subject to appropriate analytical tests, i.e. those who do not have appropriate certificates or attests.